Plant hydraulic modelling of leaf and canopy fuel moisture content reveals increasing vulnerability of a Mediterranean forest to wildfires under extreme drought - Ruffault, Julien; Limousin, Jean‐Marc; Pimont, François; Dupuy, Jean‐Luc; De Càceres, Miquel; Cochard, Hervé; Mouillot, Florent; Blackman, Chris J.; Torres‐Ruiz, José M.; Parsons, Russell A.; Moreno, Myriam; Delzon, Sylvain; et al. (The New phytologist, 2023)
Fuel moisture content (FMC) is a crucial driver of forest fires in many regions world‐wide. Yet, the dynamics of FMC in forest canopies as well as their physiological and environmental determinants remain poorly understood, especially under extreme drought. We embedded a FMC module in the trait‐based, plant‐hydraulic SurEau‐Ecos model to provide innovative process‐based predictions of leaf live fuel moisture content (LFMC) and canopy fuel moisture content (CFMC) based on leaf water potential (). SurEau‐Ecos‐FMC relies on pressure–volume ( p‐v ) curves to simulate LFMC and vulnerability curves to cavitation to simulate foliage mortality. SurEau‐Ecos‐FMC accurately reproduced and LFMC dynamics as well as the occurrence of foliage mortality in a Mediterranean Quercus ilex forest. Several traits related to water use (leaf area index, available soil water, and transpiration regulation), vulnerability to cavitation, and p‐v curves (full turgor osmotic potential) had the greatest influence on LFMC and CFMC dynamics. As the climate gets drier, our results showed that drought‐induced foliage mortality is expected to increase, thereby significantly decreasing CFMC. Our results represent an important advance in our capacity to understand and predict the sensitivity of forests to wildfires.